Vers une autonomisation du champ des sciences sociales turques - Jean-Baptiste Le Moulec (Revue des Mondes Musulmans et de la Méditerranée)
Born out of a revolution that tried to erase part of the ottoman cultural and political heritage, the Turkish Republic enrolled sciences, among which social sciences, and submitted them to its national and nationalist project. Starting in the 1990’s, after decades of isolationism, these policy-oriented sciences began to feed the debate and hereby contributed to legitimize Turkish rulers’ neo-ottoman expansionist ambitions towards the Arab Middle East. From the social science sector then emerge networks of experts discussing Turkish national foreign policy. While North-African revolutions offer a new opportunity to experts to promote the «Turkish Model », the Syrian civil war and its consequences on Turkey’s national politics, intensify the field’s ideological polarization and seems to trigger a kind of empowerment of social scientists from the political sphere.